Behavioural evidence of altered sensory attenuation in obesity. Issue 11 (November 2022) - Scarpina, Federica; Fossataro, Carlotta; Sebastiano, Alice Rossi; Bruni, Francesca; Scacchi, Massimo; Mauro, Alessandro; Garbarini, Francesca
Body ownership (i.e., the conscious belief of owning a body) and sense of agency (i.e., being the agent of one's own movements) are part of a pre-reflective experience of bodily self, which grounds on low-level complex sensory–motor processes. Although previous literature had already investigated body ownership in obesity, sense of agency was never explored. Here, we exploited the sensory attenuation effect (i.e., an implicit marker of the sense of agency; SA effect) to investigate whether the sense of agency was altered in a sample of 18 individuals affected by obesity as compared with 18 healthy-weight individuals. In our experiment, participants were asked to rate the perceived intensity of self-generated and other-generated tactile stimuli. Healthy-weight individuals showed a significantly greater SA effect than participants affected by obesity. Indeed, while healthy-weight participants perceived self-generated stimuli as significantly less intense as compared to externally generated ones, this difference between stimuli was not reported by affected participants. Our results relative to the SA effect pinpointed an altered sense of agency in obesity. We discussed this finding within the motor control framework with reference to obesity. We encouraged future research to further explore such effect and its role in shaping the clinical features of obesity.